SAT0242 Effectiveness of conventional dmard therapy in patients with rheumatoid arthritis treated under a treat to target model – lessons from a real-life cohort. (12th June 2018) - Santos-Moreno, P.; Buitrago-Garcia, D.; Villarreal, L.; Cabrera, M.; Castillo, E.; Cardozo, E.; Farietta, S.; Giraldo, R.; Gomez, D.
Abstract : Background: Rheumatoid arthritis (RA) is a common chronic inflammatory disease. It is characterized by progressive, joint damage, impaired joint function and pain, the disease causes disability and reduces quality of life. Treat-to-target (T2T) is an acknowledged management strategy for RA; it proposes that the therapeutic target in RA should be a state of remission or low disease activity. There are two types of pharmacological therapy available: biological DMARDs that are considered highly expensive for our countries and conventional DMARDs which have demonstrated effectiveness and is a low-cost treatment (1, 2). Objectives: The aim of this study was to describe global change in Disease Activity Score 28 (DAS28) using a T2T strategy during three years in a cohort of patients receiving conventional DMARDs. Methods: A descriptive cohort study was conducted. Medical records of patients from specialized in RA center were reviewed during 2015–2017; those patients were followed-up under T2T standards and a multidisciplinary approach. Clinical follow-up was according to DAS28: every 3–5 weeks (DAS28 >5.1), every 7–9 weeks (DAS28 ≥3.1 and ≤5.1), and every 11–13 weeks (DAS28 <3.1). Therapy had to be adjusted with DAS28 >3.2 unless patient's conditions don't permit it; We divided patients in four groups: remission (REM), low disease activity (LDA), moderate disease activity (MDA) and severe disease activity (SDA) patients and the aim of the study was to look at what percentage of patients reached LDA or REM. Descriptive epidemiology was done, we calculated means, and standard deviations for continuous variables and categorical variables were presented as rates. We analyzed normality for DAS28, in order to compare disease activity at beginning and the end of follow-up. Results: During 3 years we included 1953 patients were 39% were in low disease activity, 47% in moderate disease activity and 14% were in severe disease activity, 84% were female, mean age was 60 years±12. At baseline mean DAS28 was 4.45±0.90 with a median of 4.3 at three years the mean DAS28 was 3.83±1.08 with a median of 3.60. At the end of follow-up 46% of population achieved remission and 25% achieved low disease activity; at overall 71% improved disease activity, see table 1. In our study DAS28 was not normally distributed, thus we performed a Wilcoxon test in order to compare the mean DAS28 at baseline/36 months showing statistical significance (P<0.05). Conclusions: Patients treated with conventional DMARD therapy and under a T2T model achieve favorable results in regards of disease activity. This is real life evidence that can support the advantages of treating RA patients with a multidisciplinary team under a T2T model with a low-cost treatment. References: [1]Aletaha D, Alasti F, Smolen JS. Optimisation of a treat-to-target approach in rheumatoid arthritis: strategies for the 3-month time point. Annals of the Rheumatic Diseases2015. [2]Ahsan T, Erum U, Khowaja D, Dahani A. Delayed conventional DMARDs therapy is effective in Rheumatoid Arthritis. Pakistan journal of medical sciences2017;33(4):840–3. Disclosure of Interest: None declared